Estratégias competitivas e tecnologia de informação no polo calçadista de Jaú/SP - Moschetto, Danilo Augusto (Universidade Federal de São Carlos, 2017)
This thesis aims to investigate how Information Technology (IT) can support the formulation and implementation of competitive strategies in small and medium-sized companies in the footwear hub of Jaú / SP. Technological development in the areas of IT and telecommunications, especially since the end of the 20th century, has resulted in dramatic changes in society and, among the most visible effects, is the increase in communication capacity and access to information. Along with the hardware development, several systems and methods were created and implemented to support and improve various business activities: from simple spreadsheet use in customer tabulation to complete management of activities through systems such as Enterprise Resource Planning (ERP). Despite the development of IT, companies make little use of technology to support the development and deployment of their competitive strategies. Few papers in the literature discuss this relationship of support to competitive strategy, especially in the footwear industry, where literature is scarce. This study was developed in two stages: a survey was carried out, aiming to collect data on the general state of the APL (local productive arrangement) in relation to the producers of footwear and their competitive strategies, and then five case studies were carried out. The results show that companies employ diverse competitive strategies as well have different levels of automation and IT support in their tasks. Although issues related to cost, labor and training are still considered limiting factors in the implementation of support systems, some companies employ IT in the development of differentiated competitive strategies, which gives them better conditions to operate in the market. The main results of this work include, in addition to the discussion of the IT support to competitive strategies of the companies: the presentation of a scenario of the local footwear industry from the survey data, which confirmed some indications from the literature; the creation of a model of IT used by companies that includes their driving elements (legal and industry requirements, administrative complexity and support of the competitive strategy); the theoretical and practical identification of strategic actions supported by IT elements; and the discussion about how IT can help the development of competitive strategies through the support of administrative operations and the creative elements of them.
Competitive strategies and information technology at the footwear industry of Jaú/SP
Keywords: Estratégia competitiva; Tecnologia de informação; Indústria calçadista; Competitive strategy; Information technology; Footwear industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO